Factors that impact the intention of artificial intelligence adoption in retail industry among Gen Z employees in Malaysia - Chin, Zhi Kang; Low, Kai Yang; Pong, Kai Ping; Wu, Qiao Jie (2024)
Artificial Intelligence (AI) has become a game-changing technology, transforming numerous industries by automating processes, enhancing decision-making capabilities, and boosting efficiency. The retail sector has undergone significant disruption through the adoption of AI. It has empowered companies to personalize the customer experience, optimize supply chains, and streamline operations. However, the successful integration of AI in the retail industry heavily relies on the willingness and aptitude of employees, particularly the younger generation known as "Generation Z." This chapter will be structured into seven key sections, including the search background, problem statement, research objectives, research questions, hypotheses of the study, significance of the study, chapter layout, and chapter summary